Assessments of Nitrate Budgets in the Yellow Sea Based on a 3D Physical-Biogeochemical Coupled Model - Tak, Yong-Jin; Cho, Yang-Ki; Hwang, Jeomshik; Kim, Yong-Yub (Frontiers in Marine Science, 2022)
Nitrate (NO3-) plays an important role in ecosystems and aquaculture in the Yellow Sea (YS). Sparse observational data suggest that ocean currents and nitrification are crucial to NO3- flux in the YS; however, a quantitative assessment of these fluxes has not yet been performed. This study investigates seasonal and spatial variations in NO3- flux via currents and biological processes in the YS from 2006 to 2019 using a physical-biogeochemical coupled model. The model results show that the current-driven fluxes exceeded biological processes in the eastern and central regions of the YS, unlike in the western and northern regions. Advection of NO3- in the YS is mainly driven by cyclonic circulation in summer and fall, and anticyclonic circulation in spring and winter. The Subei Coastal Current along the coast of China plays a primary role in net advective influx of NO3- to the YS year round. The NO3- influx by the Yellow Sea Warm Current along the lower layer of the southcentral YS is offset by outflux through wind-driven surface currents in winter. The southward movements of the Yellow Sea Bottom Cold Water in summer and the Korean Coastal Current in winter are major NO3- outfluxes to the East China Sea. In terms of biological processes, NO3- is mainly consumed by phytoplankton during the spring bloom and supplied through organic matter decomposition and nitrification. Net supply of NO3- by biological processes was the greatest in the southcentral YS where the Yellow Sea Bottom Cold Water is present.